Hedonic Test Method for Beef Rendang With Variations in The Addition of Cinnamomum Verum - Sherly Rahmayani; Iryani Iryani; Iswendi Iswendi; Fitri Amelia (Jurnal Periodic Jurusan Kimia UNP, 2022)
Rendang is one of the typical foods of the Minangkabaunese in West Sumatra. Many people like to consume rendang because rendang has a distinctive taste because in making rendang the type of meat, coconut milk and spices used greatly affect the aroma and taste produced. The purpose of this study was to determine the level of aroma, color, texture, and taste of beef rendang with variations in the addition of Cinnamomum verum. The hedonic test of beef rendang with variations in the addition of C. verum was carried out on 50 panelists. Panelists present 6 samples with 6 different sample numbers. Panelists were asked to rate how much preference there was for the product using a hedonic scale. The hedonic test results showed that the less C. verum added, the better the taste produced. As for the aroma and color, there is no significant difference among these products